An Empirical Study on the Wear of Reciprocating Hydraulic Rod Seals Using 15 Different Oils. Issue 1 (17th October 2022) - Feuchtmüller, Oliver; Hörl, Lothar; Bauer, Frank
Abstract: Hydraulic oils differ in their chemical composition and viscosity substantially. Their influence on the wear of rod seals is neither fully understood nor can be predicted precisely. The primary objective of this study was to evaluate the influence of various oils and their wetting properties on the wear of rod seals. In an empirical study, the wear of 30 commercially available polyurethane U‐cups was investigated with 15 different oils using a recently built test rig. The wear of rod seals increased with lower viscosity and higher polarity of the oil. Both oil properties are combined in a new parameter which helps to assess the lubricity of oil and the wear of rod seals. Abstract : The primary objective of this study was to evaluate the influence of various oils and their wetting properties on the wear of rod seals. In an empirical investigation, the wear of rod seals increased with lower viscosity and higher polarity of the oil. Both oil properties are combined in a newly introduced parameter which helps to assess the lubricity of oil and the wear of rod seals.